Bifunctional primary amine 2-aminobenzimidazole organocatalyst anchored to trans-cyclohexane-1, 2-diamine in enantioselective conjugate additions of aldehydes. Issue 2 (15th February 2016) - Fernandes, Talita de A.; Vizcaíno-Milla, Pascuala; Ravasco, João M.J.M.; Ortega-Martínez, Aitor; Sansano, José M.; Nájera, Carmen; Costa, Paulo R.R.; Fiser, Béla; Gómez-Bengoa, Enrique
Graphical abstract: Abstract: Bifunctional chiral primary amine8 containing an ( S, S )- trans -cyclohexane-1, 2-diamine scaffold and a 2-benzimidazole unit is used as a general organocatalyst for the Michael addition of α, α-branched aldehydes to nitroalkenes and maleimides. The reactions take place, with 20 mol % of catalyst in dichloromethane at rt for nitroalkenes and with 15 mol % catalyst loading in toluene at 10 °C for maleimides, in good yields and enantioselectivities. DFT calculations demonstrate the bifunctional character of this organocatalyst activating the aldehyde by enamine formation and the Michael acceptor by double hydrogen bonding.